HUBUNGAN ANTARA AI AWARENESS DENGAN SELF-PERCEIVED EMPLOYABILITY PADA MAHASISWA YANG SEDANG BEKERJA - Triananda, Tizty Annur; Tulis, Laura Supalawati; Mafaza, Frisia; Saputri, Marselina; Saraswati, Kiky D. H. (Provitae: Jurnal Psikologi Pendidikan, 2025)
The rapid development of Artificial Intelligence (AI) in Indonesia has had a major impact in various fields, including the world of work. These changes require individuals, especially students who also work, to adapt in order to remain relevant to the needs of the labor market. One factor that plays a role in preparing for these challenges is AI Awareness, which is an individual's understanding of the existence, function, and impact of AI in everyday life. Meanwhile, Self-Perceived Employability relates to an individual's confidence in their ability to obtain, maintain, and develop a sustainable career. This study aims to determine the relationship between AI Awareness and Self-Perceived Employability among students who also work. This study uses a quantitative approach with convenience sampling techniques. The participants consisted of 103 students from various universities who were recruited through an online questionnaire using Google Forms. The research instruments used included two scales, namely AI Awareness and Self-Perceived Employability. The results of the data analysis showed a significant positive relationship between AI Awareness and Self-Perceived Employability among working students. The results show that the higher the students' awareness of the role and impact of AI in the world of work, the higher their confidence in obtaining, maintaining, and developing their careers. This study is expected to contribute to higher education strategies in preparing students to face the dynamics of the job market in the digital technology era.